KRITIK ILMU-ILMU KEISLAMAN: KONTRIBUSI JARINGAN ISLAM LIBERAL - FEBRI HIJROH MUKHLIS (Jurnal Ilmiah Ilmu Ushuluddin, 2019)
The Liberal Islam Network is a social-intellectual movement and policy reform group for Islamic sciences. A party that brings the discourse of emancipation and freedom of thought with concepts of pluralism, democracy, and secularism to give birth to ideas about inclusive Islam, progressive Islam, and humanist Islam. By reinterpreting the practices of the Islamic sciences, such as the study of the Qu'ran, the Kalam, the Fiqh, the Sufism, and the Philosophy, it has received much criticism as well as support for contributing to the Islamic sciences. Liberal Islamic networks want a religious definition that is humanistic, broad-based monotheism, not authoritarian, and they tend to be more transparent, inclusive and egalitarian, not simply dishonest or disbelieving to other communities. This paper will focus on two studies, first, about the movement of the Liberal Islamic Network methodology. ; Secondly, explore the contribution of the Liberal Islamic Network to the renewal of the tradition of Islamic sciences. The method used in this research is descriptive analysis with an intellectual history approach. The paper is then discussed using the theory of social movements and the scientific revolution of Thomas Kuhn. Nowadays, the Liberal Islamic Network has contributed to the development of Islamic thought, especially in the renewal of Islamic sciences.